Integrasi Pembelajaran Ips Berbasis Pendidikan Nilai Agama Untuk Meningkatkan Kompetensi Pengetahuan Dan Kompetensi Sikap - Himmatus Sa'adah (The Indonesian Journal of Social Studies, 2023)
Abstrak Penelitian  ini  bertujuan  untuk  menganalisis  kelayakan  dan  keefektifan  hasil pengembangan model integrasi pembelajaran IPS berbasis pendidikan agama, menggunakan Four-D Model  Thiagarajan. Penelitian ini sampai tahap disseminate yaitu tahap penyebaran  kepada  MGMP  guru  mata  pelajaran  IPS  kabupaten  Sidoarjo. Penelitian dilakukan di MTs Fadllillah. Model pembelajaran  IPS  berbasis  pendidikan  agama  merupakan  representasi  untuk pembelajaran berbasis agama yang menggambarkan karakteristik keterpaduan IPS dari awal hinga akhir. Dilakukan pengembangan pada : 1) kajian manusia tempat dan lingkungannya   sebagai   materi   berbasis   agama;   2)   pengorganisasian   kegiatan pembelajaran merujuk pada pembelajaran konstektual; dan 3) evaluasi pencapaian kompetensi siswa secara otentik. Berdasarkan penilaian ahli, model pembelajaran dinyatakan  layak  digunakan  dengan  skor  tertinggi  89,5%.  Berdasarkan  hasil perhitungan  rata-rata  ketuntasan  individu  pada  pretest  sebesar  30,4%  siswa dinyatakan tuntas dan posttest sebesar 78,2% siswa dinyatakan tuntas. Berdasarkan perhitungan  tersebut  terjadi  kenaikan  signifikan  yaitu  sebesar  47,8%.  Oleh sebab itu model pembelajaran dinyatakan efektif untuk meningkatkan kompetensi pengetahuan dan kompetensi sikap siswa. Kata Kunci: Model Pembelajaran, IPS, Pendidikan Agama.   Abstract This study aims to analyze the feasibility and effectiveness of the results of integrating a social studies learning model based on religious education, using the Four-D Thiagarajan Model. This research reached the disseminate stage, namely the dissemination stage to the MGMP for social studies teachers in Sidoarjo district. The research was conducted at MTs Fadllillah Tambak Sumur. The social studies learning model based on religious education is a representation for religion-based learning that describes the characteristics of the integration of social studies from the beginning to the end. Development is carried out on 1) Study of the human being, place and environment as religious-based material; 2) organizing learning activities refers to contextual learning; and 3) evaluation of student competency achievement authentically. Based on expert judgment, the learning model was declared suitable for use with the highest score of 89.5%. Based on the results of the calculation of the average individual completeness in the pretest of 30.4% of students declared complete and posttest of 78.2% of students declared complete. Based on these calculations there was a significant increase of 47.8%. The learning model is declared effective for developing knowledge and attitudes about caring for the surrounding environment through writing activities. Writing activities support the concept of humanistic psychology, namely the teacher's efforts to accept and develop students' potential. The learning model is declared effective for developing knowledge and attitudes about caring for the surrounding environment through writing activities. Writing activities support the concept of humanistic psychology, namely the teacher's efforts to accept and develop students' potential. The learning model is declared effective for developing knowledge and attitudes. Keywords: Learning Model, Social Studies, Religion Education.